Monte_Carlo_Simulations.txt - Martin, Julien; Sabatier, Quentin; Gowan, Timothy A.; Giraud, Christophe; Gurarie, Eliezer; Calleson, C. Scott; Ortega-Ortiz, Joel G.; Deutsch, Charles J.; Rycyk, Athena; Koslovsky, Stacie M. (Dryad Digital Repository, 2015)
This file includes R scripts to implement Monte Carlo simulations. It includes input information to reproduce results presented in the main text of the paper.